Tindak Tutur Ilokusi dalam Webinar BKKBN Official - Rizky Devy Wulandari; Mujid Farihul Amin; Riris Tiani (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2022)
BKKBN Official Online Seminar is a platform aimed to give information and educate people, the millenial in particular, about planned family. This study is analyzed speech on BKKBN Official Online Seminar themed